2013
DOI: 10.12965/jer.130050
|View full text |Cite
|
Sign up to set email alerts
|

Finger exercise with keyboard playing in adults with cerebral palsy: A preliminary study

Abstract: The purpose of this study is to examine the effects of Therapeutic Instrument Music Performance (TIMP) for fine motor exercises in adults with cerebral palsy (CP). Individuals with CP (n = 5) received a total of twelve, 30-min TIMP sessions, two days per week for six to nine weeks. Pre- and post-Music Instrument Digital Interface (MIDI) data were used as a measure of hand function. Pre-velocity was significantly different from the normative data obtained from typical adults (n = 20); however, post-velocity did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
1
29
0
6
Order By: Relevance
“…In one of the few published studies, five adults with CP received a total of twelve sessions of musical instrument-based therapy on MIDI keyboard, twice a week for six to nine weeks [72]. The playing speed on the keyboard increased with the training to values closer to those obtained from a control group of able-bodied individuals.…”
Section: Music-supported Therapy In Cerebral Palsymentioning
confidence: 99%
“…In one of the few published studies, five adults with CP received a total of twelve sessions of musical instrument-based therapy on MIDI keyboard, twice a week for six to nine weeks [72]. The playing speed on the keyboard increased with the training to values closer to those obtained from a control group of able-bodied individuals.…”
Section: Music-supported Therapy In Cerebral Palsymentioning
confidence: 99%
“…Recently, Schneider et al [1] showed that use of electronic drums was effective in improving stroke patients movement patterns and quality of motion. This therapeutic approach, or music-supported therapy (MST) [2], was used more recently in a preliminary study in adults with CP, in which keyboards and pianos were used [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have highlighted the potential of playing musical instruments in the rehabilitation of hand motor skills in stroke patients 8 – 11 and in adults with CP. 12 An acoustic piano provided with keystroke speed sensors has been proposed as a standard tool for the rehabilitation of professional pianists, in order to both improve motor function and assess the outcomes of treatment. 13 Beneficial effects in the rehabilitation of hand motor function are backed up by improvements in finger movement accuracy, keystroke speed, and timing accuracy.…”
Section: Introductionmentioning
confidence: 99%